Craniovertebral junction 360°: A combined microscopic and endoscopic anatomical study - Sukhdeep Singh Jhawar; Maximiliano Nunez; Paolo Pacca; Daniel Seclen Voscoboinik; Huy Truong (Journal of Craniovertebral Junction and Spine, 2016)
Objectives: Craniovertebral junction (CVJ) can be approached from various corridors depending on the location and extent of disease. A three dimensional understanding of anatomy of CVJ is paramount for safe surgery in this region. Aim of this cadaveric study is to elucidate combined microscopic and endoscopic anatomy of critical neurovascular structures in this area in relation to bony and muscular landmarks. Materials and Methods: Eight fresh frozen cadaveric heads injected with color silicon were used for this study. A stepwise dissection was done from anterior, posterior, and lateral sides with reference to bony and muscular landmarks. Anterior approach was done endonasal endoscopically. Posterior and lateral approaches were done with a microscope. In two specimens, both anterior and posterior approaches were done to delineate the course of vertebral artery and lower cranial nerves from ventral and dorsal aspects. Results: CVJ can be accessed through three corridors, namely, anterior, posterior, and lateral. Access to clivus, foreman magnum, occipital cervical joint, odontoid, and atlantoaxial joint was studied anteriorly with an endoscope. Superior and inferior clival lines, supracondylar groove, hypoglossal canal, arch of atlas and body of axis, and occipitocervical joint act as useful bony landmarks whereas longus capitis and rectus capitis anterior are related muscles to this approach. In posterior approach, spinous process of axis, arch of atlas, C2 ganglion, and transverse process of atlas and axis are bony landmarks. Rectus capitis posterior major, superior oblique, inferior oblique, and rectus capitis lateralis (RCLa) are muscles related to this approach. Occipital condyles, transverse process of atlas, and jugular tubercle are main bony landmarks in lateral corridor whereas RCLa and posterior belly of digastric muscle are the main muscular landmarks. Conclusion: With advances in endoscopic and microscopic techniques, access to lesions and bony anomalies around CVJ is becoming easier and straightforward. A combination of microscopic and endoscopic techniques is more useful to understand this anatomy and may aid in the development of future combined approaches.